Monitoramento de sistemas agroflorestais para recuperação de áreas degradadas da floresta ombrófila densa: caso Paraty-RJ - Souza, Marcia Cristina Soares de (2009)
The objective of this study was to evaluate the environmental sustainability of experimental agroforestry systems planted which aim was to restore degraded areas in a rain forest, in the municipality of Paraty, RJ. The model adopted is called as agroforestry system regenerative and analog (SAFRA), which combines leguminous and non-leguminous species in "single" (one plant /hill) and "married" (two plants/hill) planting. Thus, conical traps were installed to collect litterfall in the SAFRA systems and in a secondary forest in order to compare biomass and the intake of nutrients over a year. Individual trees were measured (circumference at breast height - CAP, commercial height - Hc; total height - Ht) and herbivory and mortality were evaluated. The forest productivity, litterfall and nutrients analyses demonstrated to be effective as environmental indicators applied to agroforestry systems. The "married" SAFRA model, independent of using leguminous or non-leguminous species presented silvicultural potential to be indicated as an agroforestry system. However, after five years, none of the SAFRA models may be considered as effective in the ecological function of restoration of riparian areas based on litterfall and nutrient when compared with secondary forest.